Framing Analysis of the Reporting of the Malang Kanjuruhan Tragedy in the Online Media - Nur Asma Robiatul Adawiyah; Catur Nugroho (Journal La Sociale, 2024)
This research aims to gain a deeper understanding of how the online media Narasi.tv frames the reality related to the riots at the Kanjuruhan Stadium in Malang. This research focuses on analyzing the framing, framing and narrative strategies used by Narasi.tv in reporting this event. By using content analysis methods, this research seeks to understand the influence and implications of the way this media presents information to the public in the context of the tragedy at the Kanjuruhan Stadium in Malang.